2022
DOI: 10.3389/fped.2021.814166
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Is Elevated in Children With Obesity and Decreases After Weight Loss

Abstract: Introduction: Childhood obesity is an increasing condition associated with continuous obesity into adulthood and development of comorbidities. Adult studies show an association between serum uric acid (SUA) levels and body mass index (BMI). The aim of this retro perspective exploratory study was to investigate SUA in obese children and adolescents and the effects of a subsequent weight reduction.Materials and Methods: One hundred and seventy-one children (age 4–18), with obesity (i.e. BMI-SDS of +2 or higher) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…Furthermore, differences in sex distribution, pubertal staging, adiposity severity, degree of central/ abdominal/visceral fat accumulation and insulin resistance as well as ethnicity might to some extent explain the variability in the prevalence of hyperuricemia and in its associations with metabolic syndrome and its components. Contrary to most other studies [20,27,38,44], we found no sex bias in hyperuricemia, even when divided by pubertal status, and SUA concentrations did not increase with age, BMI excess or waist circumference/height index. While a sex bias was inconsistent in pediatric obesity studies, the increase with age, BMI or waist circumference was a more constant nding [23,37,38,40].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, differences in sex distribution, pubertal staging, adiposity severity, degree of central/ abdominal/visceral fat accumulation and insulin resistance as well as ethnicity might to some extent explain the variability in the prevalence of hyperuricemia and in its associations with metabolic syndrome and its components. Contrary to most other studies [20,27,38,44], we found no sex bias in hyperuricemia, even when divided by pubertal status, and SUA concentrations did not increase with age, BMI excess or waist circumference/height index. While a sex bias was inconsistent in pediatric obesity studies, the increase with age, BMI or waist circumference was a more constant nding [23,37,38,40].…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, increased uric acid production by adipose tissue is also likely to contribute to hyperuricemia in obese subjects [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data, showing a significant association between reduction of BMI z-score (and WtHr) and uric acid values at follow-up, seem to support this hypothesis and also suggest that, at least in pediatric ages, if an increase in weight leads to an increase in uric acid, its reduction can reverse at least in part the phenomenon. Another recent study performed in a population of children and adolescents with obesity demonstrated a reduction in uric acid levels in children who underwent a multifactorial lifestyle intervention and lost weight during the trial, and an increase in those who gained weight [ 46 ]. In our population, the higher the uric acid values at baseline, the lower the response to the intervention, and children with uric acid values > 90th percentile at baseline were six times more likely to be hyperuricemic even at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, increased marrow adiposity is attributed to the shift from osteogenic to adipogenic differentiation of bone marrow mesenchymal stem cells ( 22 ). However, obesity is also positively associated with HU ( 23 , 24 ). Experimental evidence did suggest that purine catabolism in adipose tissue could be enhanced in obesity ( 25 ).…”
Section: Introductionmentioning
confidence: 98%